Expressions of Fib, IL-12 in Serum of Neonatal Necrotizing Enterocolitis and Their Correlation with Clinicopathological Features - Yiyu YIN; Xiaole WU; Huaxin ZOU; Shixian LI; Zhenfang QIN; Tengfei ZHANG; Junhua CAO (Tehran University of Medical Sciences, 2020)
Background: To investigate the expressions of fibrinogen (Fib) and Interleukin-12 (IL-12) in serum of neonatal necrotizing enterocolitis (NEC), and to analyze the correlation between the two and their relationship with clinicopathological features. Methods: Forty two children with NEC treated in Xuzhou Children's Hospital, Xuzhou Medical University Xuzhou, China from 2016-2019 were selected as an observation group and 40 children who underwent physical examination at the same period as a control group. The expression levels of Fib and IL-12 in the serum of two groups were detected by ELISA. The correlation between Fib and IL-12 in the observation group and the correlation among the expressions of Fib, IL-12, the clinicopathological features and common examination indexes of the children with NEC were investigated by Pearson correlation analysis. Results: The levels of Fib and IL-12 in the serum of the children in observation group were significantly higher than those in the control group were (P<0.05). There was a significant positive correlation between the levels of Fib and IL-12 in the serum of the children in observation group (P<0.05). The expression levels of Fib, IL-12 were not significantly correlated with sex and age of NEC children, but correlated with vomiting, diarrhea, bloody stool and bradycardia in NEC children (P<0.05). Fib and IL-12 were positively correlated with erythrocyte level (P<0.05) and negatively correlated with platelet level. Conclusion: The expressions of Fib and IL-12 in the serum of NEC children can objectively predict the severity of NEC.